The Effect of Social Media on Interpersonal Relationships: Study of Literature - Dwi Nur Fatmawati; Ifaddhah Soffa Ning Tiyas; Bagus Ramadhani; Hana Diendi Putri (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
Humans are social creatures who need other people to maintain their way of life. Thus, every human being definitely has the ability to interact and communicate with other people every day and with the existence of interpersonal relationships, it is now not only done directly but can be done virtually via social media. The existence of social media can make it easier for everyone to establish interpersonal relationships without any limitations of distance and time. This research aims to determine the influence of using social media as a means of interpersonal relationships. The method used in preparing this article uses a qualitative descriptive method with a literature study approach. The results of this research in online media are that relationships can be established starting from the same interest in something, such as the value of ideas or subjective views held. Meanwhile, the comfort factor is more about individuals who are looking for friends who can make them comfortable rather than friends who just waste their time with things that make them uncomfortable. Apart from that, individuals will be more comfortable if they use fake accounts in communicating in cyberspace.